Korelasi Penguasaan Ilmu Nahwu dan Ilmu Sharaf terhadap Hasil Belajar Al-Quran Hadits Siswa Kelas 12 ‘Ulya Pondok Pesantren Manhajussalikin Rokan Hulu - Roby Setyawan; Risnawati; M. Fikri Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the correlation between students’ mastery of Nahwu and Sharaf and their learning outcomes in the Al-Qur’an Hadith subject. The research employed a quantitative correlational approach and was conducted at Pondok Pesantren Manhajussalikin Rokan Hulu with students of grade XII ‘Ulya as the research subjects. The data were obtained from students’ final semester scores in Nahwu, Sharaf, and Al-Qur’an Hadith subjects and analyzed using SPSS. The results of the Pearson Product Moment correlation test indicate a strong and positive correlation between mastery of Nahwu and Al-Qur’an Hadith learning outcomes (r = 0.751, Sig. = 0.001), as well as between mastery of Sharaf and Al-Qur’an Hadith learning outcomes (r = 0.690, Sig. = 0.003). These findings show that the better the students’ mastery of Nahwu and Sharaf, the higher their learning outcomes in Al-Qur’an Hadith. Therefore, mastery of Nahwu and Sharaf plays an important role in improving students’ understanding of Al-Qur’an and Hadith texts.